In Vitro Study of the Effect of Vitamin E on Viability, Morphological Changes and Induction of Osteogenic Differentiation in Adult Rat Bone Marrow Mesenchymal Stem Cells - M Soleimani Mehranjani; A Azimi (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd, 2014)
Introduction: Vitamin E as a strong antioxidant plays an important role in inhibiting free radicals. Therefore, this study aimed to investigate the effect of vitamin E on the viability, morphology and osteogenic differentiation in bone marrow mesenchymal stem cells of an adult rat. Methods: The bone marrow mesenchymal stem cells were extracted using the flashing-out method. At the end of the third passage, cells were divided into groups of control and experimental. Experimental cells were treated withVitamin E (5,10,15,25,50,100,150μM) for a period of 21 days in the osteogenic media containing 10% of fetal bovine serum. The cell viability, bone matrix mineralization, intercellular and extracellular calcium deposition, alkaline phosphatase activity, expression of genes and synthesis of proteins of osteopontin and osteocalcin as well as morphological changes of the cells were investigated. The study data was analyzed using one-way ANOVA and T-Test setting the significant P value at P<0.05. Results: Within vitamin- E treated cells, the mean viability, mean bone matrix mineralization, calcium deposition, alkaline phosphatase activity, expression and synthesis of osteopontin and osteocalcin of the mesenchymal stem cells treated with vitamin E significantly increased in a dose dependent manner. Also cytoplasm extensions were observed in the cells treated with vitamin E. Conclusion: Since vitamin E caused a significant increase in cell viability and osteogenic differentiation in the mesenchymal stem cells, therefore it can be utilized in order to increase cell differentiation and cell survival.